Letter : Closing of Homes - Morgan, Betty
038-0096-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 4, GREAT SMITH STREET, LONDON, S.W.1. TELEPHONE: ABBEY 2565 May 5th, 1939. H.V. Tewson, Esq., Transport House, Smith Square, London, S.W.1. Dear Mr. Tewson, CLOSING OF HOMES. This is to inform you that there will be a meeting of the Sub-Committee in connection with the Closing of Homes, on Wednesday, May 10th, at 4.50 p.m., at this address. It is very much hoped that you will be able to attend. Yours sincerely, for BETTY MORGAN [signed] Organizing Secretary. 292/946/38/96